The Influence of Digital Leadership on Millennial Employee Performance in East Java Mediated by Employee Creativity - Nandaffa Maulina; Emma Yulianti (Jurnal Manajemen dan Kewirausahaan, 2024)
This study aims to analyze and test the influence of digital leadership on employee performance mediated by employee creativity. The research sample consisted of 135 respondents who met the criteria as employees aged 27-42 years and worked in companies in East Java province. Data were analyzed using the structural equation modeling technique using SmartPLS 3.0. The results of the study showed that digital leadership had a significant positive effect on employee performance and employee creativity, while employee creativity had a significant positive effect on employee performance. In addition, employee creativity was able to mediate the relationship between digital leadership and employee performance.